2001
DOI: 10.1002/1097-0320(20010201)43:2<101::aid-cyto1024>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in cytogenetic slide preparation: Controlled chromosome spreading, chemical aging and gradual denaturing

Abstract: Background: Metaphase spreading is an essential technique for clinical and molecular cytogenetics. Results of classical banding techniques as well as complex fluorescent in situ hybridization (FISH) applications, such as comparative genomic hybridization (CGH) or multiplex FISH (M-FISH), are greatly influenced by the quality of chromosome spreading and pretreatment of the slide prior to hybridization. Materials and Methods: Using hot steam and a metal plate with a temperature gradient across its surface, a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(103 citation statements)
references
References 11 publications
1
102
0
Order By: Relevance
“…In contrast, Henegariu et al (2) specified no ambient conditions and used hot steam to moisten the slides and then put them on a 65-75°C metal plate, which, according to our own tests, dries the slides in 10 s. Whereas some researchers dropped cells on dry slides (4,5), others suggested that having a thin layer of water on the slides immediately before adding the cells improves spreading (1,2,6). Dropping cells from a height reportedly enhanced chromosome spreading (1,3), but others have disagreed (2,7). Aware of the "mysterious aspects" of chromosome spreading, Barch et al (10) suggested that it is more of an "art" than science.…”
mentioning
confidence: 81%
“…In contrast, Henegariu et al (2) specified no ambient conditions and used hot steam to moisten the slides and then put them on a 65-75°C metal plate, which, according to our own tests, dries the slides in 10 s. Whereas some researchers dropped cells on dry slides (4,5), others suggested that having a thin layer of water on the slides immediately before adding the cells improves spreading (1,2,6). Dropping cells from a height reportedly enhanced chromosome spreading (1,3), but others have disagreed (2,7). Aware of the "mysterious aspects" of chromosome spreading, Barch et al (10) suggested that it is more of an "art" than science.…”
mentioning
confidence: 81%
“…Fluorescent in situ hybridization was performed on freshly made slides 'aged' chemically as described by Henegariu et al (2001).…”
Section: Centromeric and Telomeric Signals In Nucleoplasmic Bridgesmentioning
confidence: 99%
“…In brief, PBL metaphase and prometaphase chromosomes for FISH analysis were performed as described by Henegariu [7]. DNA probe preparation: Chromosome microdissection was performed according to previously described methods [8,9].…”
Section: Metaphase Chromosome Preparationsmentioning
confidence: 99%